Employment trends in the Northern Great Plain’s Region - Szabó, Fanni (Acta Agraria Debreceniensis, 2012)
Hungary can be divided into 7 regions, of which I am writing about the Northern Great Plain Region in this article. The Northern Great Plain consists of the counties Hajdú-Bihar, Jász-Nagykun-Szolnok, and Szabolcs-Szatmár-Bereg. There are 389 settlements in the region, which can be considered rather few. The population of the region is nearly 1.5 million, which is nearly 15% of the total  population. This region is one of the most disadvantageous regions in Hungary, with its economic indicators ranking the lowest of all regions. Nevertheless, as regarding education and agriculture, the region is considered to be a prominent area.